Pengaruh Facebook Terhadap Interaksi Sosial Peserta Didik di MAN 1 Palu - Nur Eka Wahyuningsih Riyadi (Universitas Tadulako, 2023)
The purpose of this study was to determine the effect of using Facebook on the social interaction of students at MAN 1 Palu. This research is quantitative research with a survey method. The results showed that there was a significant influence between the use of Facebook on the social interaction of students at MAN 1 Palu. This can be seen from the tcount (6.156) > ttable (1.663), then is rejected and is accepted and the coefficient of determination of this study shows the contribution of the influence of the independent variable (X ), namely the use of Facebook on the dependent variable (Y ) namely the social interaction of students at MAN 1 Palu by 49% while the rest is influenced by other variables. This research is expected to be information material for parents and educators to control students in using Facebook as a means of social interaction and especially for students to use Facebook in good ways and not overuse it, so that the negative impact of using Facebook can be prevented and avoided especially if the impact makes students have an anti-social attitude towards the surrounding environment.